Portal Vein and Superior Mesenteric Vein Invasion of Hydatid Cyst of The Liver: Surgical Treatment Option - Ali Sapmaz; Egemen Cicek; Serhan Yilmaz; Hakan Bolukbasi; Ahmet Soykurt; Selcuk Mevlut Hazinedaroglu (Lietuvos Chirurgija)
Hydatid cyst is a parasitic infestation by a tapeworm of the genus Echinococcus granulosus which can be localized in all vascularized tissues and causes cystic lesions. We present a case of hydatid liver cyst with portal vein and superior mesenteric artery invasion. Hydatid cysts are still commonly seen in Turkey. We believe that the most efficacious and least morbid treatment alternative for such rare complications of hydatid cysts is surgery.